Rethinking domestic politics of Indonesian SSTC in Africa and paradox of MRLs education training - Muhammad Ridha Iswardhana; Poppy Sulistyaning Winanti; Ririn Tri Nurhayati (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
Indonesia attempted to use its foreign policy to address domestic and international objectives in its relations with other nations. Due to Indonesia's success in the 1955 AAC and involvement in the 1961 NAM, the country's administration used the SSTC mechanism to further local goals. Indonesia often offers Muslim Religious Leaders (MRLs) international reproductive health training to bring SSTC to African nations. Analysis of domestic politics and international aid used in this research. Using secondary data from literature studies, this research employs a qualitative explanatory case study methodology. In addition, triangulation analysis based on theory and Nvivo classification based on analysis of domestic politics and foreign aid are applied. This research found Indonesia tried to project itself as a nation that successfully and consistently implements and promotes family planning worldwide. However, various paradoxes exist in how Indonesian SSTC is implemented through MRLs activities. Indonesia has a high level of foreign debt, which goes against religious belief, and the notion that a large family is necessary for success is the opposite of the success of Indonesian SSTC.